Information and Communication Technologies in Tourism 2023 Proceedings of the ENTER 2023 eTourism Conference, January 18-20, 2023 - Ferrer-Rosell, Berta; Massimo, David; Berezina, Katerina; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This open access book provides an extensive overview of the usage of information and communication technologies in the tourism and hospitality industry. It presents the proceedings of the International Federation for IT and Travel & Tourism (IFITT)$1 (Bs 30th Annual International eTourism Conference, which assembles the latest research presented at the ENTER2023 conference. The enclosed papers cover various topics within the field, including augmented and virtual reality, website development, social media use, e-learning, big data, analytics and recommendation systems.s
The Initial Impact of Technology Enabled Relationship Creation in Rural Lebanon -- Meaning of fun in hotel gamified applications -- Riding against the algorithm: Algorithmic management in on-demand food delivery -- (3z(BDomestic or International?(3y (BThe Impact of Cognitive Absorption of Short-Form Videos on Tourists$1 (BPost-COVID Travel Intention: An exploratory study on Douyin -- A Re-rank Algorithm for Online Hotel Search -- Exploring Customer Experience with Service Robots in Hospitality and Tourism: Activity Theory Perspective -- How do affect the infusion of smart technology and mindfulness of tourism SMEs on competitiveness -- User Experience and Spatial Presence in a Walk-in Augmented Reality 3D Model for Tourists.s
Keywords: Tourism; Management; Artificial intelligence; Business information services; Industrial management -- Environmental aspects; Tourism Management; Artificial Intelligence; IT in Business; Corporate Environmental Management